Transfer pricing under an origin based VAT system - Bernd Genser; Günther G. Schulze (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper analyzes transfer pricing incentives under a destination-based and an origin-based VAT system. While a switch to the origin-based VAT may moderate or reinforce the incentive for transfer pricing induced by income tax differentials, we show that in the case of the EU this switch tends to reduce the transfer pricing incentive and thus should remove one of the last major objections against the adoption of an origin-based VAT system in the EU.
Keywords: H21; H26; H87; F15; 330; International taxation; transfer pricing; value-added taxation